Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer: y=-2x-3 = x=-1/2y+-3/2
5x = -4+ y = x=1/5y+-4/5
proof:
y=-2x-3 -- Step 1: Flip the equation.
−2x−3=y
Step 2: Add 3 to both sides.
−2x−3+3=y+3
−2x=y+3
Step 3: Divide both sides by -2.
−2x/-2=y+3/-2
5x = -4+ y -- Step 1: Divide both sides by 5.
5x/5=y-4/5
Answer:
they are both simplified already, theres nothing else you can do with them
Step-by-step explanation:
im not sure exactly what they are looking for but there is nothing else you can do there except put it in different froms like slope intercept and standard form
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.